Pengecilan gelombang tekanan dan kilasan dalam konkrit - Kamarudin Mohd. Yusof,; Mohamad Pauzi Ismail, (1994)
The use of relative amplitude of ultrasonic waves to evaluate concrete quality is described in this paper. Other than frequency, the scattering of pressure and shear waves is also influenced by inhomogenieties of the propagated media. The attenuation of pressure and shear waves due to scattering differ for certain frequency. Experiments to examine the correlation between concrete compressive strength with relative amplitude of pressure/shear waves and velocity were performed. The results of experiment show that relative amplitude and pressure wave velocity have a good correlation with strength. Finally, a model of combined velocity and relative amplitude is proposed